Sonographic Ultrasound Evaluation of Mastalgia and to Determine the Relationship between Breast Duct Diameter and Severity of Mastalgia - Aziz, Sundus; Sattar, Amjad; Walid, Ayesha; Rahim, Anila; Naz, Nasreen; Ara, Husson (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To determine the breast ultrasound findings in patients with Mastalgia and the relationship between breast duct diameter and severity of Mastalgia. METHODOLOGY: A prospective cross-sectional study carried out at Dow Institute of Radiology, Dow University of Health Sciences from June-December 2021. Female patients, irrespective of age, presenting with Mastalgia without any prominent finding on clinical examination were included. A fellowship-trained radiologist performed an ultrasound. Data analysis was performed on SPSS 22.0 RESULTS: Total 380 patients were included. The mean age of the patients was 36.3±11.5 years, and the mean VAS score was 3.2±1.2. A total of 234(61.6%) had mild pain, 139(36.6%) had moderate pain and 7(1.8%) had severe pain. The mean duct diameter in patients with Mastalgia was 2.9±3.7 mm, with 220(57.9%) patients having a diameter <2.0 mm and 160(42.1%) having a diameter >2.0 mm. Duct ectasia was found in 161(42.4%). Mastalgia was significantly higher in patients with duct ectasia (p-value <0.001) and in patients with fibrocystic change (p-value <0.001). CONCLUSION: Duct ectasia, fibrocystic changes, infective/inflammatory changes, and axillary lymphadenopathy were sonographic features of Mastalgia. Mastalgia was significantly higher in patients with duct ectasia, duct diameter >2.0 mm and in patients with fibrocystic changes. Keywords: Mastalgia, Duct ectasia, fibrocystic changes, breast pain.